Determination of reactive power flow in deregulated transmission system - Mohd Herwan, Sulaiman; Mohd Wazir, Mustafa; Omar, Aliman; Ismail, Daut, Prof. Dr. (Institut Teknologi Brunei, 2011)
Organize by Institut Teknologi Brunei , 3rd – 4th November 2008 at Rizqun International Hotel, Gadong Bandar Seri Begawan, Brunei Darussalam.